Contribution of TGF-Beta-Mediated NLRP3-HMGB1 Activation to Tubulointerstitial Fibrosis in Rat With Angiotensin II-Induced Chronic Kidney Disease - Zhang, Kaimin; Fan, Chun; Cai, Dongpeng; Zhang, Yi; Zuo, Rui; Zhu, Li; Cao, Yue; Zhang, Jian; Liu, Chao; Chen, Yang; Liang, Hui (Frontiers in Cell and Developmental Biology, 2020)
Fibrosis is a common phenotype that often leads to the progression of blood pressure-induced chronic kidney disease (CKD). TGF-beta plays an important role in promoting pathogenesis,and NLRP3 is a critical mediator in the progression of blood pressure-induced CKD. However, the pathophysiological roles of the TGF-beta- mediated NLRP3 pathway in modulating fibrosis in blood pressure-induced CKD have not been elucidated. The present study aims to investigate the contribution of TGF-beta-mediated NLRP3 inflammasome to renal fibrosis in mice with high blood pressure. By treating rats with angiotensin II (Ang II) for 14 days, we observed development of CKD,characterized by increased levels of blood pressure, epithelial–mesenchymal transition (EMT) markers(alpha-smooth muscle actin [alpha- SMA], MMP-2,and MMP-9)and fibrosis. Immunohistochemical analysis further revealed that TGF-beta and NLRP3 inflammasome activation(high-mobility group box 1 [HMGB1], IL-1beta, and NLRP3)was significantly upregulated in the kidney of rats with Ang II-induced hypertension. Interestingly,we observed that Ang II could not increase the production of NLRP3 proteins, but TGF-beta could induce NLRP3 protein expression in cultured rat tubular epithelial cells. Furthermore,we speculated that TGF-beta played a pathogenic role in Ang II-induced CKD because TGF-beta induced the activation of NLRP3 inflammasomes and Gasdermin D expression. We also proved that the pharmacological inhibition of NLRP3 by ISO caused a decrease in TGF-beta-induced NLRP3 inflammasome activation and increased the expression of EMT markers (alpha-SMA and collagen I) and Gasdermin D expression. Collectively, these results suggest that TGF-beta-mediated NLRP3 inflammasome activation may cause the release of HMGB1 and increase in Gasdermin D in tubular epithelial cells, thereby contributing to renal fibrosis in Ang II-induced CKD. These findings provide novel insights into the pathogenic role of NLRP3 in CKD associated with high blood pressure.